Low cost assistive technology to support educational activities for adolescents with cerebral palsy. (3rd October 2018) - da Silva, Alan Patricio; Bulle Oliveira, Acary Souza; Pinheiro Bezerra, Italla Maria; Pedrozo Campos Antunes, Thaiany; Guerrero Daboin, Blanca Elena; Raimundo, Rodrigo Daminello; dos Santos, Vagner Rogério; de Abreu, Luiz Carlos
Abstract: Introduction: The concept of assistive technology covers several areas of action; one of them is communication with the elaboration of accessible solutions to overcome daily difficulties. It contributes to the resumption of functional abilities, expanding and facilitating inclusion and independent living. Objective: To analyze the usability of a low cost prototype device to support educational activities of adolescents with cerebral palsy. Methods: A descriptive observational study. The evaluation of a prototype device was made through a validated questionnaire, Quest Version 2.0, on the level of the user's satisfaction with an assistive technology, composed of 12 evaluation items. The questionnaire was filled out by the educator based on the observation of four wheelchair-bound participants diagnosed with cerebral palsy according to the international classification of diseases and health-related problems, ICD-10, who attend a coexistence and teaching institution in the state of São Paulo, Brazil. Results: The device developed was considered an assistive technology, which provided an experience with a positive level of satisfaction for the participants. Conclusion: The tested prototype contributes to communication and interaction allowing adolescents with cerebral palsy to participate in educational activities. Implications for Rehabilitation: The device assists the individual in the educational activities and can positively influence their development, observe the individual number 5, who has an important limitation in coordination and fine movements, placing the role of the task in the vertical position offers a new perspective to perform the task, this stimulates him to try to perform the work, so the challenge was adjusted to the demands of each individual which can contribute to its neuromotor development, the amplitude of the distal movements and the manual ability, since it must look for alternatives to complete the task requested.